A review of the geometrical basis and the principles underlying the use and interpretation of the video head impulse test (vHIT) in clinical vestibular testing - Curthoys, Ian S.; McGarvie, Leigh A.; MacDougall, Hamish G.; Burgess, Ann M.; Halmagyi, Gabor M.; Rey-Martinez, Jorge; Dlugaiczyk, Julia (Frontiers in Neurology, 2023)
This paper is concerned mainly with the assumptions underpinning the actual testing procedure, measurement, and interpretation of the video head impulse test—vHIT. Other papers have reported in detail the artifacts which can interfere with obtaining accurate eye movement results, but here we focus not on artifacts, but on the basic questions about the assumptions and geometrical considerations by which vHIT works. These matters are crucial in understanding and appropriately interpreting the results obtained, especially as vHIT is now being applied to central disorders. The interpretation of the eye velocity responses relies on thorough knowledge of the factors which can affect the response—for example the orientation of the goggles on the head, the head pitch, and the contribution of vertical canals to the horizontal canal response. We highlight some of these issues and point to future developments and improvements. The paper assumes knowledge of how vHIT testing is conducted.